Clinical, Radiological and Pathological evaluation of breast lumps: a crosssectional study from a tertiary care hospital of north-east India - Kaushik Datta; Kaushik Datta; Susmita Dutta (Global Journal of Medicine and Public Health, 2025)
ABSTRACT